Unilateral pulmonary collapse in asthmatics. - Hopkirk, J A (1978)
Five asthmatic patients developed collapse of one lung. Three of the patients were children and three of the five had repeated episodes of atelectasis. Episodes of atelectasis were usually associated with localised chest pain, which was not pleuritic in character, and with breathlessness, but without wheezing. The were not related to clinically apparent respiratory infections or to deterioration of the underlying asthma. The cause is obscure, but re-expansion seems to be hastened by oral corticosteroid therapy.